Animation from pencils to pixels classical techniques for digital animators - White, Tony (Routledge, 2017)
Award-winning animator Tony White brings you the ultimate book for digital animation. Here you will find the classic knowledge of many legendary techniques revealed, paired with information relevant to today's capable, state-of-the-art technologies.White leaves nothing out. What contemporary digital animators most need to know can be found between this book's covers - from conceptions to creation and through the many stages of the production pipeline to distribution. This book is intended to serve as your one-stop how-to animation guide. Whether you're new to animation or a very experienced digital animator, here you'll find fundamentals, key classical techniques, and professional advice that will strengthen your work and well-roundedness as an animator.